Examining Cross-Age Experiences in a Distance-Based Intergenerational Music Project: Comfort and Expectations in Collaborating With Opposite Generation Through “Virtual” Exchanges - Belgrave, Melita J.; Keown, Daniel J. (Frontiers in Medicine, 2018)
There has been an increase in the number of music-based intergenerational programs conducted by music therapists as part of wellness and intergenerational music therapy programs. Research has shown that intergenerational music therapy programs have improved cross-age attitudes, interactions, and older adults’ psychosocial well-being. Anecdotal evidence indicates that one of the challenges for creating music-based intergenerational programs is finding agencies that serve younger and older generations within close proximity to one another. We sought to remedy this problem with the integration of “virtual” technology. The purpose of this study was to examine changes in cross-age comfort, expectations after experiencing “virtual” exchanges, and preconceived notions of older and younger persons enrolled in a distance-based intergenerational project. A secondary purpose was to determine what intergenerational project factors were most enjoyable for older and younger participants. Eighteen older adults (61 through 79 years old) from an intact music-therapy choir along and 14 younger children from an intact community choir (9 through 14 years old) served as participants for the current study. All participants experienced the four-week distance-based intergenerational program that consisted of: a) two group “virtual” exchanges, b) two reflective journals related to the “virtual” exchanges, c) an in-person half-day music-therapy intergenerational workshop, and d) a joint performance. Cross-age comfort, preconceived notions, expectations, and preference factors were examined through pre-test and post-test measurements. Results indicated an increase in older adults’ comfort level collaborating with children after participation in the intergenerational music project. The majority of younger (64%) and older (69%) participants indicated that their preconceived notions about the other generation were different and positive from what they initially thought prior to the project. Both generations indicated an improvement in cross-age attitudes and interactions due to the collaboration process (“virtual” exchange, workshop, and joint-performance) and the cross-age interactions during the project. These findings suggest that music therapists can foster cross-age interactions and relationships between generations that are not within close proximity of one another by using a combination of “virtual” and “live” interactions as an intervention for enhancing the overall quality of life among older adults.